The Electronic Bee Spy: Eavesdropping on Honeybee Communication via Electrostatic Field Recordings - Paffhausen, Benjamin H.; Petrasch, Julian; Greggers, Uwe; Duer, Aron; Wang, Zhengwei; Menzel, Simon; Stieber, Peter; Haink, Karén; Geldenhuys, Morgan; Čavojská, Jana; Stein, Timo A.; Wutke, Sophia; et al. (Frontiers in Behavioral Neuroscience, 2021)
As a canary in a coal mine warns of dwindling breathable air, the honeybee can indicate the health of an ecosystem. Honeybees are the most important pollinators of fruit-bearing flowers, and share similar ecological niches with many other pollinators; therefore, the health of a honeybee colony can reflect the conditions of a whole ecosystem. The health of a colony may be mirrored in social signals that bees exchange during their sophisticated body movements such as the waggle dance. To observe these changes, we developed an automatic system that records and quantifies social signals under normal beekeeping conditions. Here we describe the system and report representative cases of normal social behavior in honeybees. Our approach utilizes the fact that honeybee bodies are electrically charged by friction during flight and inside the colony, and thus they emanate characteristic electrostatic fields when they move their bodies. These signals, together with physical measurements inside and outside the colony (temperature, humidity, weight of the hive, and activity at the hive entrance) will allow quantification of normal and detrimental conditions of the whole colony. The information provided instructs how to setup the recording device, how to install it in a normal bee colony, and how to interpret its data.